2016
DOI: 10.17795/mejrh-34020
|View full text |Cite
|
Sign up to set email alerts
|

The Golden Proportion in Dentistry: A Literature Review

Abstract: Context: Divided attention is impaired in the early stages of Alzheimer's disease (AD). The influence of divided attention on people with AD has been considered from different perspectives, such as motor ability, cortical responses, performance in divided attention evaluation tasks, and comparison of divided attention and directed and focused attention. The purpose of the current study was to investigate divided attention in AD patients from these different perspectives.Evidence Acquisition: An electronic sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Beauty is said to be power, a smile is its sword. The perception of dental esthetics varies significantly among dental professionals, although substantial efforts have been made to establish common standards [1] [2]. Research in the area of aesthetic perception has identified different factors that contribute to a beautiful face [3] like: sexual dimorphism, ethnic background, genetics, and environment [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beauty is said to be power, a smile is its sword. The perception of dental esthetics varies significantly among dental professionals, although substantial efforts have been made to establish common standards [1] [2]. Research in the area of aesthetic perception has identified different factors that contribute to a beautiful face [3] like: sexual dimorphism, ethnic background, genetics, and environment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the tooth di-mensions varied somewhat by race and gender, the ratios were quite consistent. However, the golden proportion was not found to correlate with any of the calculated ratios [2] [11].…”
Section: Introductionmentioning
confidence: 99%
“…We examine the arch of the smile, the proportion between the height and the width of the teeth, and finally the relation between the widths of the teeth and the golden proportion. [5][6][7][8][9][10][11][12] Model analysis cannot be omitted in making an exact diagnosis.…”
Section: Introductionmentioning
confidence: 99%